Visit Satisfaction And Intention Of Gen Z Muslim Tourists In Jakarata Influenced By Halal Destination Attributes - Mahardiyanto, Agus; Wulandari, Deasy; Naqiyya, Nihal Rannan; Ariyanti, Rini (Ekonomi Bisnis, 2023)
Halal is becoming a global phenomenon, market trend and lifestyle. Along with the increasing number of Muslim travellers, interest in halal tourism is also growing. The increasing number of Muslim travellers is a challenge and opportunity to improve Indonesia's tourism industry. The tourism industry itself plays an important role in increasing Indonesia's state revenue. The purpose of the study was to analyse the effect of halal destination attributes on visit satisfaction and intention of gen Z Muslim tourists in Jakarta. The sample in this study were 150 respondents. The method used in this study is path analysis with halal Destination Attributes as the independent variable, visiting satisfaction as the intervening variable, and intention as the dependent variable. Data processing uses t test and sobel test. The test results show that the destination attribute variable shows a significant number. This means that Jakarta is considered a city that has advantages in the ease of information and communication to tourists, services and facilities are also adequate, as well as the environment and comfort as a tourist destination.